Can Early Rehabilitation after Total Hip Arthroplasty Reduce Its Major Complications and Medical Expenses? Report from a Nationally Representative Cohort. (4th June 2015) - Chiung-Jui Su, Daniel; Yuan, Kuo-Shu; Weng, Shih-Feng; Hong, Rong-Bin; Wu, Ming-Ping; Wu, Hing-Man; Chou, Willy
Abstract : Objective . To investigate whether early rehabilitation reduces the occurrence of posttotal hip arthroplasty (THA) complications, adverse events, and medical expenses within one postoperative year. Method . We retrospectively retrieve data from Taiwan's National Health Insurance Research Database. Patients who had undergone THA during the period from 1998 to 2010 were recruited, matched for propensity scores, and divided into 2 groups: early rehabilitation (Early Rehab) and delayed rehabilitation (Delayed Rehab). Results . Eight hundred twenty of 999 THA patients given early rehabilitation treatments were matched to 205 of 233 THA patients given delayed rehabilitation treatments. The Delayed Rehab group had significantly (all p < 0.001 ) higher medical and rehabilitation expenses and more outpatient department (OPD) visits than the Early Rehab group. In addition, the Delayed Rehab group was associated with more prosthetic infection (odds ratio (OR): 3.152; 95% confidence interval (CI): 1.211–8.203; p < 0.05 ) than the Early Rehab group. Conclusions . Early rehabilitation can significantly reduce the incidence of prosthetic infection, total rehabilitation expense, total medical expenses, and number of OPD visits within the first year after THA.